Basin planning framework for irrigation salinity management - Skogerboe, G.V.; Aslam, M. (1994)
A planning framework for developing best management practices for salinity management in a river basin is presented. For purposes of analysis, the basin is divided into subareas. First, an inflow-outflow analysis is undertaken that describes, in general, the mass balance flow of water and salts between all of the subareas within the basin. A salinity management model is used for the detailed analysis within each subarea. This model consists of: (1) hydro-salinity submodel; (2) soil moisture chemistry submodel; (3) groundwater salinity submodel. Finally, cost-effectiveness analysis are undertaken, first of all for each subarea, which are then aggregated into a set of optimal cost effectiveness functions for the entire basin, that facilitates decision-making in establishing an appropriate basin-wide salinity management program.